2017
DOI: 10.1002/jsfa.8411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brassica oleracea early stage abiotic stress responses reveals tolerance in multiple crop types and for multiple sources of stress

Abstract: Abiotic stress tolerance was identified in multiple B. oleracea crop types, with some lines exhibiting resistance to multiple stresses. For each stress, no one crop type appeared significantly more or less tolerant than others. The results are promising for the development of more environmentally robust lines of different B. oleracea crops by identifying tolerant material and highlighting the relationship between responses to different stresses. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…For all the other cultivars and seasons, the weight was around 400 to 450 g per inflorescence, with no significant differences. It has been reported that when multiple abiotic stresses were applied to different Brassica oleracea L. crop types, no relevant differences were found among them, which is promising for the development of more environmentally robust lines (Beacham et al, 2017). Therefore, if we consider the different temperatures and day lengths of the seasons as additional stresses to salinity, this can explain the differing responses of the cultivars studied.…”
Section: Discussionmentioning
confidence: 99%
“…For all the other cultivars and seasons, the weight was around 400 to 450 g per inflorescence, with no significant differences. It has been reported that when multiple abiotic stresses were applied to different Brassica oleracea L. crop types, no relevant differences were found among them, which is promising for the development of more environmentally robust lines (Beacham et al, 2017). Therefore, if we consider the different temperatures and day lengths of the seasons as additional stresses to salinity, this can explain the differing responses of the cultivars studied.…”
Section: Discussionmentioning
confidence: 99%
“…The increased popularity of broccoli is largely due to its many desirable nutrients, antioxidants, and other bioactive compounds [ 2 , 4 ]. Broccoli is considered a cool season crop and, like many crops, is vulnerable to several abiotic stresses that might limit productivity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A series of short-term abiotic stress assays have recently been developed to screen B. oleracea lines for resilience to drought, waterlogging, high salinity, heat and freezing stress ( Figure 1 and Beacham et al, 2017). This study used assay systems that aimed to provide a close approximation of transplant stress while allowing sufficient throughput for effective population screening.…”
Section: Studies In Leafy Vegetable Cropsmentioning
confidence: 99%
“…An example assay system for the investigation of short-term stress resilience in Brassica oleracea (Beacham et al, 2017). Brassica oleracea seedlings are grown in module trays to the 3–4 true leaf stage before the imposition of short-term (<1 week) stress treatments.…”
Section: Improving Crop Stress Resiliencementioning
confidence: 99%